Hubungan antara Hipertensi dan Kematian Pasien COVID-19 di Layanan Rawat Inap RSUD Tarakan Tahun 2022 (Association between Hypertension and Mortality of COVID-19 Inpatients at Tarakan Regional General Hospital in 2022) - Widyasari, Karina; Sudaryo, Mondastri Korib (Jurnal Epidemiologi Kesehatan Indonesia, 2024)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 was the leading disease in terms of the highest number of hospital admissions and cause of death at the Tarakan Regional General Hospital (RSUD Tarakan) in 2022. COVID-19 patients who received treatment at the hospital were often individuals with underlying conditions, such as hypertension. Therefore, it is important to conduct research on comorbidities, specifically hypertension, and its relationship to COVID-19 mortality at the RSUD Tarakan’s inpatient in 2022, so the hospital can design spesific care plans for COVID-19 patients with hypertension. This study used a retrospective cohort design with secondary data from the RSUD Tarakan's SIMRS reports. A total of 534 samples met the criteria for analysis. The variables measured included COVID-19 mortality, patient’s age and gender, hypertension, type 2 Diabetes Mellitus (DM), heart failure, Chronic Kidney Disease (CKD), Acute Kidney Injury (AKI), sepsis, and Acute Respiratory Distress Syndrome (ARDS). Analysis was performed using cox proportional hazards regression. The results showed a significant association between hypertension and COVID-19 mortality (aRR= 0.406; 95% CI 0.250-0.659; p-value: 0.000) after controlling for age. This indicates that patients with hypertension were 59.4% less likely to die from COVID-19 compared to those without hypertension. It is important to note that there are other factors that were not considered in this study. Therefore, the researchers suggest conducting further studies which take into account the severity of hypertension and the impact of antihypertensive treatment on COVID-19 mortality.